BAT algorithm used for load balancing purpose in cloud computing: an overview. (28th September 2020) - Ullah, Arif; Nawi, Nazri Mohd; Khan, Mubashir Hayat
Cloud computing is modern technology that has led to significant change in different fields of life by providing different kinds of servicer like hardware and software on user demands based on pay and gain rule. Due to the rapid growth of cloud computing it faces different kinds of issues, and resource allocation is one of them. For the improvement of resource allocation system in cloud computing different kinds of technique are used, and load balancing technique is one of them. In this paper we discuss resource allocation system in virtual machines (VM) because when a user sends data in VM then a situation may occur that some VM are overloaded and some become underloaded, which may lead to failure of system or request delay. For improvement of this situation different researchers used different algorithms in load balancing technique for cloud computing. This paper only focuses on BAT algorithms which are used for load balancing technique in improved resource allocation system for VM and also defines those rules which are used for improvement in load balancing technique in cloud data centre.